Die Messung individueller Vergebungstendenz im SOEP: Skaleneigenschaften der deutschen Version der Tendency-to-Forgive-Scale - Michael Weinhardt; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This documentation presents the scale characteristics of a new scale measuring people's tendency to forgive. The tendency to forgive is understood here as an individual disposition to forgive other people when one has suffered injustice or harm from them. The scale is a German translation of a scale already validated in the USA. The scale was first tested in the 2009 SOEP Pretest (N=1,007) and showed satisfactory reliability and validity under the typical conditions of population surveys (low number of items, high heterogeneity of respondents). The convergent validity was tested based on the Big Five Personality dimensions as well as a scale measuring reciprocal behavior. Based on the satisfactory results from the pretest, the scale was included in 2010 in the main SOEP survey (N=18,913). Our evaluation of the reliability and factor structure using data from the main survey confirmed the results from the pretest.
Keywords: 330; Soziale Beziehungen; Persönlichkeitspsychologie; Messung; Panel; Deutschland